IMPROVE STUDENTS' READING COMPREHENSION USING NARRATIVE TEXT THROUGH THINK-PAIR-SHARE TECHNIQUES - Berliana, Ainun; Imam Sudarmaji (PROGRES PENDIDIKAN, 2025)
This article aims to investigate the application of the think-pair-share method to improve narrative text reading skills in grade X students of SMK Kihajar Dewantara, Jambe. The research design used is classroom action research (PTK). The research instruments used are observations, field notes, and tests. The subject of the study was grade X students of SMK Kihajar Dewantara, Jambe consisting of 26 students. There are two success criteria in this study. First, if 80% of students actively participate in the learning process, and second if 80% of students get a minimum score of 75 as the minimum score criterion (KKM). The results showed that there were two rounds to implementing the think-pair-share method successfully. The results of the study in cycle 1 showed 16% of students could exceed the minimum score. Therefore, the first round has not been successful, and it is necessary to make improvements to the treatment given. In cycle 2, 58% of students were able to exceed the minimum score limit of 75.